Developing employee’s technical skills: the relationship between training effectiveness and employees performance / Khairiyah Abdul Hamid - Abdul Hamid, Khairiyah (Faculty of Business and Management, 2011)
Project paper titled “DEVELOPING EMPLOYEE’S TECHNICAL SKILLS: THE RELATIONSHIP BETWEEN TRAINING EFFECTIVENESS AND EMPLOYEES PERFORMANCE” is conducted as partial requirement to fulfil the requirement as needed by the faculty of Business Management, MARA University of Technology (UITM). The intention of this study is to identify the most factors that affecting the job performance among employees in the Amanahraya Berhad as the scope study in this research and the significant relationship between factors influencing their job performance. The researcher chooses to use descriptive research design as method and the researcher use survey in order to gain the data. Data used in this research are primary and secondary data such as journal and books. Researcher also use questionnaire to attain the data in order to get the feedback from Amanahraya Berhad’s employees.